Analisis Sistem Human Interface (HMI) pada Kompetensi Programmable Logic Controller (PLC) - Angga Septian MN; Dian Megasari (Teknik Informatika Universitas Pamulang, 2020)
This analysis aims to determine the difference between Human Machine Interface (HMI) based learning media and conventional learning media in influencing student competence in operating the Programmable Logic Controller (PLC). The method used was a true experimental design with a posttest-only control group design. The experimental group was given learning treatment assisted by HMI Omron with the CX-Designer software, while the control group was given treatment with conventional learning media. The treatment effect was analyzed by using different test (Mann-Whitney). The results showed that the effect of HMI-based learning media on PLC competence is as follows: (1) 61% competence in the cognitive domain is in the very good category, 50% competence in the affective domain is in the very good category, and 50% competence in the psychomotor domain is in the very good category; and (2) There are competency differences between HMI-based learning media and conventional learning. This is evidenced by the Sig. Count value of 0.000 in the cognitive domain, 0.000 in the affective domain, and 0.001 in the psychomotor domain, which is smaller than the Sig. Of the study of 0.05 after being given treatment.